A Simple Enrichment Correction Factor for Improving Erosion Estimation by Rare Earth Oxide Tracers. Issue 12 (14th December 2017) - Zhang, X.C. (John); Liu, G.; Zheng, F.L.
Abstract : Core Ideas: Rare‐earth element oxide tracers are preferably bound to silt and clay particles. Rare‐earth element tracers are conservative during erosion and transport in each size class. A simple correction factor reduced erosion estimation error to greater than 4.5%. The correction method does not require rare‐earth element measurement in different classes. The rare‐earth element technique is capable of producing high‐quality erosion data. Spatially distributed soil erosion data are needed to better understand soil erosion processes and validate distributed erosion models. Rare‐earth element (REE) oxides have been extensively tested and used to trace soil movement at plot or small watershed scales to generate spatial erosion data. However, a general concern regarding the accuracy of the technique arose due to selective binding of REE to fine soil particles and their preferential transport during soil erosion by water. Our objective was to develop a simple enrichment correction factor to improve the accuracy of the technique without the need for measuring REE for multiple size classes. A coarse Lithic Ustipsamment soil (2% clay, 20% silt), deliberately tagged with eight REE oxides, was packed into eight zones in a physical model of a small watershed to trace erosion from each zone. Three 30‐min rains were simulated at 1, 1.5, and 2 mm min −1, and runoff was collected every 2 min. Sediment was separated into nine size classes, and REE oxides in each class were extracted and analyzed by inductively coupled plasma–mass spectrometry. Both REE and the silt + clay fraction (<0.05 mm) were enriched in the sediment, resulting in a consistent overestimation of soil loss. An enrichment correction factor, based on enrichment of the <0.05‐mm fraction, effectively corrected the overestimation and reduced the event mean estimation errors from 18 to 40% to <4.5%. The correction circumvents the need for measuring REE for multiple size classes, which is costly and time consuming. Moreover, this study found that REE tracers were conservative within each size class during erosion, and this scientifically underpins the use of an enrichment correction factor and erosion tracing by multiple size classes. The correction factor should be further tested with different soils.